(untitled) (Journal of Educational Sciences, 2026)
The study examines the preparation of future primary school teachers for effective collaboration with tutors and support specialists in the context of inclusive education for children with autism spectrum disorder (ASD). The relevance of the research is determined by the increasing number of children with ASD in mainstream schools and the growing demand for teachers who possess interdisciplinary competencies necessary for organizing high‑quality support. The aim of the study is to assess the readiness of 3rd and 4th year students majoring in “Pedagogy and Methods of Primary Education” at Korkyt Ata Kyzylorda University (n=144) and to develop a scientifically grounded model for training teachers to support the educational process of children with ASD. The methodology includes a Likert-scale questionnaire (25 items, M=3.2±0.9), content analysis of 10 academic courses revealing a 72% content deficit, and the piloting of a four-stage model incorporating ABA modules and simulation-based training. The findings indicate an overall moderate level of readiness among students (58%), insufficient knowledge of ABA methods (32%), and challenges in teamwork. Implementation of the proposed model resulted in a 56% average increase in students’ competencies (t=9.5, p<0.001).The scientific novelty lies in substantiating the structure of professional readiness and applying an interdisciplinary approach. The practical significance is reflected in the development of recommendations for universities in Kazakhstan, aligned with the Concept of Inclusive Policy of the Republic of Kazakhstan for 2025–2030. Keywords: inclusive education, ASD, tutor, teacher training, primary classes, team interaction.